Oracle performance tuning for 10gR2 - Powell, Gavin; Powell, Gavin (Burlington, MA : Digital Press, 2007)
Tuning of SQL code is generally cheaper than changing the data model. Physical and configuration tuning involves a search for bottlenecks that often points to SQL code or data model issues. Building an appropriate data model and writing properly performing SQL code can give 100%+ performance improvement. Physical and configuration tuning often gives at most a 25% performance increase. Gavin Powell shows that the central theme of Oracle10gR2 Performance Tuning is four-fold: denormalize data models to fit applications; tune SQL code according to both the data model and the application in relation to scalability; create a well-proportioned physical architecture at the time of initial Oracle installation; and most important, mix skill sets to obtain the best results. * Fully updated for version 10gR2 and provides all necessary transition material from version 9i * Includes all three aspects of Oracle database tuning: data model tuning, SQL & PL/SQL code tuning, physical plus configuration tuning * Contains experienced guidance and real-world examples using large datasets Emphasizes development as opposed to operating system perspective.
pt. 1. Data model turning -- The relational database model -- Turning the relational database model -- Different forms of the relational database model -- A brief history of data modeling -- pt. 2 SQL code tuning -- What is SQL? -- The basics of efficient SQL -- Advanced concepts of efficient SQL -- Common-sense indexing -- Oracle SQL optimization and statistics -- How Oracle SQL optimization works -- Overriding optimizer behavior using hints -- How to find problem queries -- 10g automated SQL tuning -- pt. 3. Physical and configuration tuning -- Tuning Oracle database file structures -- Object tuning -- Low-level physical tuning -- Hardware resource usage tuning -- Tuning network usage -- Oracle partitioning and parallelism -- pt. 4. Tuning everything at once -- Ratios: possible symptoms of problems -- Wait events -- Latches -- Tools and utilities -- The wait event interface -- 9i tuning with STATSPACK.
Previous ed. published: New York : Digital Press, c2004, under title: Oracle high performance tuning for 9i and 10g.
Includes index.
Keywords: Relational databases; Oracle (Computer file); Electronic books